Memristive Ferroelectric FET for 1T-1R Nonvolatile Memory With Non-Destructive Readout - Roopesh Singh; Shivam Verma (IEEE Open Journal of Nanotechnology)
Energy-efficient non-volatile memory that supports non-destructive read capabilities is in high demand for random-access memory applications. This article presents the proposal and demonstration of a 1T-1R non-volatile memory cell, which has distinct read and write paths that utilize a memristive variant of the ferroelectric field effect transistor (MFeFET) for data storage. Through a combination of experimentally calibrated models and TCAD-based mixed-mode simulations, the proposed MFeFET-based memory cell is demonstrated to achieve a non-destructive read operation and higher read current at low operating voltages. Furthermore, the memory cell demonstrates a 50% reduction in read latency compared to spin transfer torque (STT) magneto-resistive random-access memory (MRAM) technologies, positioning it as a highly efficient solution for next-generation non-volatile memory applications.